Method for producing carbon composite iron ore
The method addresses the challenge of producing strong coal-containing agglomerate ores for blast furnaces by using a specific process involving metallic iron, calcium oxide compounds, and controlled moisture and treatment steps, achieving the required strength even with high carbon content raw materials.
Patent Information
- Application Number
- JP2023147331
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Existing methods struggle to produce coal-containing agglomerate ores with sufficient strength for use in blast furnaces, especially when the carbon content is 2.5% by mass or more.
A method involving a preparation step with particulate matter containing metallic iron and calcium oxide compounds, followed by moisture control, cold compression and aggregation, water immersion, and static treatment to produce agglomerates with enhanced strength.
The method effectively produces coal-containing agglomerate ores with crushing strengths suitable for blast furnace use, even when using raw materials with high carbon content.
Smart Images

Figure 2025040491000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing carbon-containing agglomerates. [Background technology]
[0002] Currently, most iron is produced by the blast furnace method. A blast furnace is a facility that produces pig iron from iron raw materials. Sintered ore, pellets, and lump ore, which are iron raw materials and iron oxide, are charged into the blast furnace from the top. Coke, which is both a reducing agent and a fuel, is also charged. Inside the furnace, iron ore is reduced by the reducing agent to produce pig iron. In addition to the above, the iron raw materials charged into a blast furnace include carbon-containing agglomerated ores (sometimes called carbonaceous ores), which are made by adding carbon to fine ore or steelmaking dust and agglomerating them.
[0003] It is known that charging carbon-containing agglomerates into a blast furnace promotes the reduction reaction and improves the gas utilization rate (for example, Non-Patent Document 1). Therefore, carbon-containing agglomerates are expected to contribute to improving the productivity of blast furnaces and reducing the fuel ratio. Furthermore, it has been proposed to charge carbon-containing agglomerates together with coke into a vertical furnace such as a cupola and reduce and melt them to produce molten pig iron. It is also considered that carbon-containing agglomerates can be used in electric furnaces.
[0004] In recent years, it has become difficult to collect scrap with a low content of tramp elements such as copper, and the use of reduced iron agglomerates (HBI, etc.) in which the iron has been partially reduced in electric furnaces has been considered. However, since this reduced iron is not completely reduced, it is considered necessary to make the agglomerates contain carbon to promote the reduction of iron oxide in the electric furnace.
[0005] Hereinafter, the carbon-containing iron raw material charged into a blast furnace, an electric furnace, or the like will be referred to as "carbon-containing agglomerate", and the raw material for producing the carbon-containing agglomerate will be simply referred to as "raw material". As technologies relating to carbon-containing agglomerate, for example, Patent Documents 1 to 4 are known.
[0006] Also, a technology is known for producing carbon-containing agglomerates by cold compressing and agglomerating powdered reduced iron (particulate material) containing metallic iron (for example, Patent Document 5). When compressed and agglomerated, the metallic iron contained in the powdered material interlocks with each other and is pressed and bonded due to its plasticity. Furthermore, by subjecting the produced carbon-containing agglomerates to a water immersion and standing treatment, a part of the metallic iron is oxidized and bonded, thereby increasing the strength of the obtained carbon-containing agglomerates. That is, in the method for producing agglomerates described in Patent Document 5, metallic iron is used as a binder. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-92833 [Patent Document 2] Patent No. 3502008 [Patent Document 3] Patent No. 5503364 [Patent Document 4] Patent No. 5503495 [Patent Document 5] Patent No. 5512205 [Non-patent literature]
[0008] [Non-Patent Document 1] Mamoru Inoue and 4 others, "Iron and Steel", The Iron and Steel Institute of Japan, 1986, Vol. 72, No. 12, p.S885 Summary of the Invention [Problem to be solved by the invention]
[0009] From the viewpoint of exerting the effect of promoting the reduction reaction, the carbon content of the carbon-containing agglomerates is preferably 2.5 mass% or more. However, when the carbon content of the carbon-containing agglomerates increases, the strength of the carbon-containing agglomerates decreases. In this case, when the carbon-containing agglomerates are charged into a blast furnace, it becomes difficult to ensure the ventilation inside the furnace. If the strength of the carbon-containing agglomerates is too low, the carbon-containing agglomerates may be damaged by vibrations and impacts during transportation and conveyance.
[0010] In the manufacturing method described in Patent Document 5, even if the powdered ore contains carbon, it is considered possible to obtain a high-strength carbon-containing agglomerated ore by increasing the content of metallic iron. However, it is not easy to manufacture a powdered ore with a high content of metallic iron. In Example 3-1 of the Examples in Patent Document 5, Portland cement is added to make the Portland cement content 8 mass%, thereby manufacturing a carbon-containing agglomerated ore with a carbon content of 3.3 mass%. However, Portland cement contains silicon dioxide and aluminum oxide, which are impurities or harmful components in the iron-making process. For this reason, it is preferable to avoid adding high-silicon binders such as Portland cement to the carbon-containing agglomerated ore as much as possible. A high-silicon binder means a material in which the ratio of the concentration of silicon dioxide to the concentration of calcium oxide contained is 0.2 or more (SiO2 / CaO≧0.2), the total iron content is less than 10 mass%, and the carbon is less than 5 mass%. In this specification, a substance with a total iron content of 10 mass % or more is called an "iron source", and a substance with a carbon content of 5 mass % or more is called a "carbonaceous material".
[0011] As described above, even if the manufacturing method described in Patent Document 5 is simply used, it is not easy to obtain carbon-containing agglomerates having a carbon content of 2.5 mass % or more and high enough strength for use in a blast furnace.
[0012] An object of the present disclosure is to provide a method for producing carbon-containing agglomerates, which can produce carbon-containing agglomerates having strength usable in a blast furnace even when using raw materials having a carbon content of 2.5 mass% or more. [Means for solving the problem]
[0013] The method for producing carbon-containing agglomerates according to the present disclosure includes a preparation step, a moisture adjustment step, an agglomeration step, a water immersion step, and a settling step. In the preparation step, a powdery ore containing metallic iron and a calcium oxide-containing compound is prepared. The powdery ore has a total iron content of 10 mass% or more on a dry basis, a carbon content of 2.5 mass% or more, and a ratio of the total amount of calcium to the total amount of silicon of 2.9 to 6.1 in mass ratio. Furthermore, the metallic iron content a, calcium oxide content b, and carbon content c of the powdery ore satisfy the following formula (1). In the moisture adjustment step, the moisture contained in the powdery ore is adjusted to 0.5 mass% or more and 7.0 mass% or less. In the agglomeration step, after the moisture adjustment step, the powdery ore is cold compressed and agglomerated to form an agglomerate. In the water immersion step, the agglomerate is subjected to a water immersion treatment. In the standing step, the agglomerates are subjected to a standing treatment after the water immersion step. 400≦(2340×a+3300×b-400)×(1-5.5×c) (1) Effect of the Invention
[0014] According to the method for producing carbon-containing agglomerates according to the present disclosure, even when raw materials having a carbon content of 2.5 mass % or more are used, carbon-containing agglomerates having a strength sufficient for use in a blast furnace can be produced. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a diagram showing the crushing strength of tablets produced using Samples A to G. [Diagram 2] FIG. 2 is a flow diagram of the manufacturing method according to the embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing an example of a manufacturing process flow. [Figure 4] FIG. 4 is a cross-sectional view of the agglomeration apparatus used in the manufacturing method according to the embodiment. [Diagram 5] FIG. 5 is a schematic diagram showing an example of a manufacturing process flow. [Figure 6] FIG. 6 is a schematic diagram showing the tableting process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] As described above, even if the manufacturing method described in Patent Document 5 is simply used, it is not easy to manufacture carbon-containing agglomerates having a strength usable in a blast furnace. Therefore, in order to solve the above problem, the present inventors have intensively studied manufacturing conditions that affect the strength of carbon-containing agglomerates. As a result, the present inventors have found that when a powdery material containing a calcium oxide-containing compound in addition to metallic iron is used as a raw material, even if the powdery material contains carbon, the decrease in strength of the obtained carbon-containing agglomerates can be suppressed. This is because the strength of the manufactured carbon-containing agglomerates is increased by oxidizing and bonding a part of the metallic iron in the powdery material and by carbonating a part or all of the calcium oxide-containing compound in the powdery material. Furthermore, it has been found that by adjusting the total amount of calcium and the total amount of silicon contained in the powdery material, carbon-containing agglomerates having a strength usable in a blast furnace can be manufactured even if the powdery material contains carbon.
[0017] Here, the above-mentioned "calcium oxide-containing compound" is a general term for compounds containing calcium, such as dicalcium silicate (2CaO·SiO2), tricalcium silicate (3CaO·SiO2), calcium aluminate (3CaO·Al2O3), calcium hydroxide (Ca(OH)2), and calcium carbonate (CaCO3), in addition to pure calcium oxide (free lime, CaO). In this specification, dicalcium silicate and tricalcium silicate may be collectively referred to as calcium silicate.
[0018] A powdered or granular substance containing a calcium oxide-containing compound may contain not only pure calcium oxide but also compounds containing calcium such as di-calcium silicate. In this specification, the "calcium oxide content" in such a powdered or granular substance means the calcium oxide content when it is assumed that all of the calcium contained in the compound exists as calcium oxide. The calcium oxide content of the powdered or granular substance is calculated as follows. First, the calcium content of compounds other than pure calcium oxide is converted to the calcium content when the calcium exists as calcium oxide. Then, the content obtained by the conversion is added to the content of pure calcium oxide. This gives the calcium oxide content of the powdered or granular substance.
[0019] For example, suppose that the powdered or granular material contains dicalcium silicate in addition to pure calcium oxide, and the content of pure calcium oxide is 10 mass% (0.10), and the content of calcium contained in dicalcium silicate is 5 mass% (0.05). In this case, the content of calcium oxide in the powdered or granular material is calculated as follows. If the calcium contained in dicalcium silicate exists as calcium oxide, the content is 7 mass% (=5 mass%×56.1g / 40.1g) because the mass per mole of calcium is 40.1g and the mass per mole of calcium oxide is 56.1g. By adding this content to the content of pure calcium oxide (10 mass%), the content of calcium oxide is calculated to be 17 mass% (0.17). In Tables 1 to 8 described later, values calculated in this way may be shown as the content of calcium oxide.
[0020] The inventors then investigated the relationship between the metallic iron content, calcium oxide content, and carbon content of the powdery granular material and the strength of the carbon-containing agglomerated ore. First, powdery granular material samples A to G with different metallic iron content, calcium oxide content, and carbon content were prepared. No high silicon binder such as cement was added to each of the samples A to G. These powdery granular materials were cold agglomerated (tabletted), and then immersed in water and left to stand to produce tablets. The crushing strength of the tablets obtained using each of the samples A to G was measured. The components of each of the samples A to G are shown in Table 1. In Table 1, the total iron content (mass%) is represented as T.Fe, and the metallic iron content (mass%) is represented as m.Fe. The same notation may be applied to Tables 2 to 8 described later.
[0021] [Table 1]
[0022] The powdered and granular materials of Samples A to C were produced by reducing iron ore. The powdered and granular materials of Samples D to E were produced by subjecting iron-based waste materials to a reduction roasting process. The calcium oxide content of Samples A to C was less than 0.1 mass%, and the average of Samples D to F was 16.0 mass%. In other words, the calcium oxide content of Samples A to C was substantially 0 (zero), and the calcium oxide content of Samples D to F was substantially 0.16.
[0023] Sample G was produced by adding coke powder to sample E. The carbon content of sample G was 4.9 mass% (0.049). The components of the coke powder are shown in Table 5 below. The carbon content of the coke powder was analyzed in accordance with JIS M8812 (2006). That is, the ash and volatile content of the coke were measured, and the value obtained by subtracting these from 100 (=100-(ash)-(volatile)) was determined as the carbon content of the coke. The ash content is the mass fraction (%) of the amount of ash remaining when the sample is heated and incinerated at 815°C in air to the entire sample before heating and incineration. The volatile content is the value obtained by placing the sample in a crucible with a lid, heating it at 900°C for 7 minutes while avoiding contact with air, and calculating the mass fraction (%) of the amount of ash reduced by heating to the entire sample before heating.
[0024] Fig. 1 is a diagram showing the crushing strength of tablets produced using samples A to G. In Fig. 1, the vertical axis indicates the crushing strength, and the horizontal axis indicates the content of metallic iron in the powdered or granular material. In this specification, the content means a ratio without units, unless otherwise specified.
[0025] 1, the tendency of crushing strength relative to the metallic iron content is clearly different between Samples A to C and Samples D to F. In the case of Samples A to C, i.e., when the calcium oxide content is 0, the tablet crushing strength Y1 is expressed by the approximate formula "Y1 = 2340 x a - 400", where a is the metallic iron content. Similarly, in the case of Samples D to F, i.e., when the calcium oxide content is 0.16, the tablet crushing strength Y2 is expressed by the approximate formula "Y2 = 2340 x a + 130".
[0026] The equations for Y1 and Y2 are linear functions, and the proportionality coefficient is the same for both equations. Comparing equations Y1 and Y2, it can be said that when the metallic iron content in the granular material is the same, and the calcium oxide content increases from 0 to 0.16, the crushing strength increases by 530 N / piece (=(130-(-400))). When the metallic iron content is constant, and the crushing strength is expressed as a linear function of the calcium oxide content, the proportionality coefficient of the equation is 3300 N / piece (≒530 / 0.16). In other words, when the calcium oxide content increases from 0 to b, the increase in crushing strength, ΔY, is expressed as "3300×b". The above formula for Y1 represents the crushing strength when the calcium oxide content is 0, so by adding ΔY to the formula for Y1, the crushing strength Y3 of a tablet made from a powdered material with a metallic iron content of a and a calcium oxide content of b can be derived. This crushing strength Y3 can be expressed as "Y3 = 2340 x a + 3300 x b - 400" using the metallic iron content a and calcium oxide content b.
[0027] Here, the carbon content of samples D to F is very small and can be considered to be substantially 0 (zero). The crushing strength of sample G, which has a carbon content of 0.049, is reduced by 0.27 (27% by mass) compared to the crushing strength of a sample with the same metallic iron content but substantially zero carbon content. With the same metallic iron content in the powdered material, if the carbon content increases by 1% by mass (0.01), the crushing strength can be said to decrease by 5.5 (=0.27 / 0.049)% by mass (0.055). In other words, the crushing strength when the carbon content is c can be obtained by multiplying the crushing strength when the carbon content is 0 by (1-5.5×c). The above formula Y3 represents the crushing strength when the carbon content is 0, so by multiplying the formula Y3 by (1-5.5×c), the crushing strength Y of a tablet (carbon-containing agglomerate) containing carbon produced from granular material with metallic iron content a, calcium oxide content b, and carbon content c can be derived. From the above, it is estimated that the crushing strength Y of carbon-containing agglomerate can be expressed as "Y=(2340×a+3300×b-400)×(1-5.5×c)" using metallic iron content a, calcium oxide content b, and carbon content c.
[0028] The raw materials charged into a blast furnace are required to have high strength in order to ensure gas permeability inside the furnace. The crushing strength of carbon-containing agglomerates needs to be 400 N / piece or more. Therefore, if the metallic iron content a, calcium oxide content b, and carbon content c in the powdered and granular material are adjusted so that the crushing strength Y calculated from the above formula is 400 N / piece or more, carbon-containing agglomerates strong enough to be used in a blast furnace can be produced.
[0029] The above formula was calculated in a test using agglomerates produced by tableting (hereinafter, also referred to as the tableting test). The reason for adopting the tableting test in this study is as follows. In addition to tableting, briquetting is another method for agglomerating powdery and granular materials. In tableting, as shown in Fig. 6, which will be described later, a powdery and granular material is filled into a closed mold, and the filled powdery and granular material is compressed by a piston to form a desired shape. On the other hand, in briquetting, as shown in Fig. 4, which will be described later, the powdery and granular material is supplied between two rotatable rolls, and compressed while slipping due to friction with the roll surfaces. This brings the raw material particles closer to each other, and agglomerates with fewer voids and high density are obtained. Furthermore, as the roll gap gradually decreases, the powdery and granular material is compressed, and agglomerates with higher density and strength than those by tableting are easily obtained. Therefore, if the agglomerates produced by tableting can have the necessary crushing strength, it is believed that the agglomerates produced by briquetting under the same raw material conditions can also have the necessary crushing strength. Therefore, a tableting test, which is difficult to obtain the crushing strength, was adopted as the test for calculating the above formula.
[0030] The method for producing carbon-containing agglomerates according to the embodiment of the present disclosure has been completed based on the above findings.
[0031] The method for producing carbon-containing agglomerates according to the embodiment includes a preparation step, a moisture adjustment step, an agglomeration step, a water immersion step, and a settling step. In the preparation step, a powdery ore containing metallic iron and a calcium oxide-containing compound is prepared. The powdery ore has a total iron content of 10 mass% or more, a carbon content of 2.5 mass% or more, and a ratio of the total amount of calcium to the total amount of silicon of 2.9 to 6.1 in mass ratio on a dry basis. Furthermore, the metallic iron content a, calcium oxide content b, and carbon content c of the powdery ore satisfy the following formula (1). In the moisture adjustment step, the moisture contained in the powdery ore is adjusted to 0.5 mass% or more and 7.0 mass% or less. In the agglomeration step, after the moisture adjustment step, the powdery ore is cold compressed and agglomerated to form an agglomerate. In the water immersion step, the agglomerate is subjected to a water immersion treatment. In the standing step, after the water immersion step, the agglomerates are subjected to a standing treatment (first configuration). 400≦(2340×a+3300×b-400)×(1-5.5×c) (1)
[0032] In the first configuration of the manufacturing method, first, a powdered ore containing carbon is prepared. Specifically, the powdered ore has a total iron content of 10 mass% or more, a carbon content of 2.5 mass% or more, and a ratio of the total amount of calcium to the total amount of silicon of 2.9 to 6.1 in mass ratio on a dry basis. By making the carbon content 2.5 mass% or more, when the manufactured carbon-containing agglomerated ore is used in a blast furnace, it is expected to have significant effects such as a reduction in fuel ratio and an improvement in productivity. However, by making the powdered ore contain carbon, it becomes difficult to maintain the strength of the obtained carbon-containing agglomerated ore. Therefore, in the first configuration of the manufacturing method, after adjusting the moisture contained in the powdered ore, the powdered ore is compressed and agglomerated to manufacture an agglomerated product. Furthermore, the agglomerated product is subjected to a water immersion treatment and a static treatment. When the metallic iron contained in the powdered ore is compressed and agglomerated, it is interlocked with each other due to its plasticity and is bonded by being pressed. Furthermore, by subjecting the produced agglomerates to water immersion and standing treatment, a part of the metallic iron is oxidized and bonded, and the strength of the resulting carbon-containing agglomerates is increased. In other words, metallic iron is used as a binder. Also, by carbonating a part or all of the calcium oxide-containing compounds in the powdery and granular material, it is possible to suppress a decrease in the strength of the produced carbon-containing agglomerates, even if raw materials containing carbon are used.
[0033] In the preparation process, the ratio of the total amount of calcium (Ca) and the total amount of silicon (Si) contained in the powdered and granular material is adjusted to be 2.9 or more by mass ratio. Calcium silicates such as di-calcium silicate and tri-calcium silicate are one of the above-mentioned calcium oxide-containing compounds. These are also strength-producing components contained in cement, and harden by carbonation. Dicalcium silicate is a compound in which the ratio of the total amount of calcium (Ca) and the total amount of silicon (Si) is 2.9 by mass ratio. Tri-calcium silicate is a compound in which the ratio of the total amount of calcium and the total amount of silicon is 4.3 by mass ratio. Therefore, by setting the ratio of the total amount of calcium (Ca) and the total amount of silicon (Si) contained in the powdered and granular material to 2.9 or more by mass ratio, calcium silicate is easily contained in the powdered and granular material. This further increases the strength of the produced carbon-containing agglomerated ore. However, if the raw material contains excessive calcium, the amount of material to be processed increases, and production efficiency decreases. Therefore, the ratio of the total amount of calcium to silicon must be 6.1 or less by mass.
[0034] Furthermore, in the preparation step, the metallic iron content a, calcium oxide content b, and carbon content c of the powdery and granular material are adjusted to satisfy the above formula (1). The right side of formula (1) corresponds to the crushing strength of the raw material when the powdery and granular material is compressed and agglomerated, and the agglomerates are subjected to water immersion treatment and static treatment to produce carbon-containing agglomerates. In other words, when the powdery and granular material satisfying the above formula (1) is used as the raw material, the crushing strength of the obtained carbon-containing agglomerates is 400 N / piece or more. Therefore, according to the manufacturing method of the first configuration, even when a raw material with a carbon content of 2.5 mass% or more is used, carbon-containing agglomerates having a strength usable in a blast furnace can be produced.
[0035] In the preparation step of the manufacturing method of the above configuration, the metallic iron content a of the powdery ore is preferably 10 mass% or more (second configuration). In the manufacturing method of the second configuration, the metallic iron is sufficiently contained in the powdery ore. Therefore, agglomeration by meshing and compression of the metallic iron particles and oxidation bonding of the metallic iron are promoted, and the strength of the carbon-containing agglomerated ore can be more reliably ensured.
[0036] In the preparation step of the manufacturing method of the above configuration, the calcium oxide content b of the powdered ore is preferably 10% by mass or more and 40% by mass or less (third configuration). In the manufacturing method of the third configuration, the calcium oxide-containing compound is sufficiently contained in the powdered ore. Therefore, carbonation of the calcium oxide-containing compound in the powdered ore is promoted, and the strength of the carbon-containing agglomerated ore can be more reliably ensured. However, if the powdered ore contains an excessive amount of calcium oxide, the amount of the object to be compressed and agglomerated in the agglomeration step increases, thereby decreasing the production efficiency. Therefore, in the manufacturing method of the third configuration, the calcium oxide content b is 40% by mass or less.
[0037] In the preparation step of the manufacturing method configured as above, the content of the high silicon-based binder in the powdered or granular material on a dry basis is 2 mass% or less (fourth configuration). High silicon-based binders such as Portland cement contain calcium silicate and calcium aluminate, which contribute to strength development. However, high silicon-based binders contain silicon dioxide and usually aluminum oxide. These are unnecessary or harmful components in blast furnace operation. In addition, when a high silicon-based binder is added, the cost of preparing and mixing the binder increases compared to when no binder is added. From this viewpoint, it is preferable that the high silicon-based binder is not added to the powdered or granular material as much as possible. More preferably, no high silicon-based binder is added to the powdered or granular material.
[0038] In the preparation step of the manufacturing method configured as above, preferably, a powdery or granular material is manufactured by subjecting raw materials including iron-based waste to a reducing roasting treatment (fifth configuration). Zinc is a harmful component that can cause trouble in blast furnace operation. In the manufacturing method of the fifth configuration, a raw material including iron-based waste is subjected to a reducing roasting treatment. As a result, even if the iron-based waste contains iron oxide and zinc, reduced iron from which zinc has been separated and removed can be produced. That is, a powdery or granular material from which zinc has been removed (powdered reduced iron) is manufactured.
[0039] In the preparation step of the manufacturing method of the above configuration, the raw material may contain iron-based waste material, carbonaceous material, and calcium-containing material. The iron-based waste material or carbonaceous material contains a silicon-containing material. In this case, the ratio of calcium to silicon contained in the raw material is 2.9 to 6.1 in mass ratio (sixth configuration). In the manufacturing method of the sixth configuration, the powdered or granular material has a ratio of the total amount of calcium (Ca) to the total amount of silicon (Si) of 2.9 to 6.1 in mass ratio at the raw material stage, i.e., before the reduction roasting treatment is performed. Therefore, calcium silicate is easily generated in the reduction roasting treatment.
[0040] In the preparation step of the manufacturing method of the above configuration, the calcium-containing substance contained in the raw material may be in the form of a slurry in which lime powder is suspended in water (seventh configuration). In the manufacturing method of the seventh configuration, the calcium-containing substance contained in the raw material is in the form of a slurry in which very fine lime powder is suspended in water, so that the contact efficiency between the calcium-containing substance and the silicon-containing substance contained in the raw material is high. This improves the reactivity between the calcium-containing substance and the silicon-containing substance, and during the reduction roasting process, it becomes easier to produce di-calcium silicate, which is a component contained in cement and has a large strength development effect.
[0041] In the preparation step of the manufacturing method configured as above, the reducing roasting treatment may be performed at a temperature lower than 1300°C (eighth configuration). If the reducing roasting treatment is performed at 1300°C or higher, deposits are likely to form and grow on the inner wall of the reducing furnace used in the reducing roasting treatment. In the manufacturing method of the eighth configuration, the reducing roasting treatment is performed at a temperature lower than 1300°C, so that the low-melting point substance can be prevented from being significantly molten and the significant growth of deposits on the inner wall of the reducing furnace can be prevented.
[0042] In the preparation step of the manufacturing method of the above configuration, reduced iron may be produced by a reduction roasting process. In this case, the mass ratio of metallic iron to the iron content contained in the reduced iron is 0.8 or less (ninth configuration). When the content of metallic iron contained in the powdered ore is increased, it becomes easier to obtain a high-strength carbon-containing agglomerate even when a raw material containing carbon is used. From the viewpoint of use in a blast furnace, it is desirable that the iron metallization rate is high. The iron metallization rate is the content (mass%) of metallic iron relative to the total content (mass%) of iron. However, a huge amount of energy is required to obtain reduced iron with a high metallization rate. In addition, when trying to obtain reduced iron with a high metallization rate, there is a risk of problems such as sticking, in which the reduced iron particles stick to each other. For this reason, in the powdered ore produced by the reduction roasting process, it is practical to set the mass ratio of metallic iron to the iron content contained in the reduced iron to 0.8 or less.
[0043] In the agglomeration step of the manufacturing method configured as above, the powdery granular material may be compressed and agglomerated using an agglomeration device, and then sieved to separate the agglomerated material, which is an oversize product, and the powdery granular material, which is an undersize product. In this case, the powdery granular material, which is the undersize product, is supplied to the agglomeration device and compressed and agglomerated again (tenth configuration). The particle size of the undersize product in the agglomeration step is finer than the particle size of the powdery granular material after the preparation step and the moisture adjustment step. Therefore, by mixing the undersize product in the agglomeration step with the powdery granular material after the preparation step and the moisture adjustment step, the packing density is increased when the powdery granular material is compressed and agglomerated using the agglomeration device. Therefore, agglomerated material with high crushing strength can be easily obtained.
[0044] In the manufacturing method having the above configuration, the mass of each agglomerate after the standing step is preferably 40g or less (eleventh configuration). The larger the mass of each carbon-containing agglomerate produced, the higher the productivity. However, if the mass is too large, the impact of dropping the carbon-containing agglomerate during transportation and conveyance becomes large, and the raw material is easily damaged. For this reason, the weight of each agglomerate after the standing step is preferably 40g or less, and more preferably 30g or less.
[0045] In the leaving step of the manufacturing method of the above configuration, the leaving treatment is preferably performed in an atmosphere of 5°C or more and less than 50°C (12th configuration). In the manufacturing method of the 12th configuration, the leaving treatment is performed in an atmosphere of 5°C or more and less than 50°C in the leaving step, which promotes carbonation of the calcium oxide-containing compound in the agglomerates and oxidation of metallic iron. This improves the strength of the carbon-containing agglomerates.
[0046] In the agglomeration step of the manufacturing method configured as above, preferably, a double-roll briquette molding machine is used to compress and agglomerate the powdery or granular material (thirteenth configuration). In the manufacturing method of the thirteenth configuration, a double-roll briquette molding machine is used to compress and agglomerate the powdery or granular material. In the compression and agglomeration using a double-roll briquette molding machine, the powdery or granular material is supplied between two rotating rolls and compressed and molded. Agglomerates having high density and strength are manufactured by the compression and agglomeration using a double-roll briquette molding machine. Furthermore, the operation of the double-roll briquette molding machine is continuous, resulting in high productivity.
[0047] Hereinafter, a specific example of the method for producing carbon-containing agglomerates according to the present embodiment will be described with reference to the drawings. In the drawings, the same or corresponding parts are designated by the same reference characters and the description thereof will not be repeated.
[0048] [First embodiment] [Manufacturing method of carbon-containing agglomerates] A method for producing carbon-containing agglomerates according to the present embodiment will be described with reference to Figs. 2 and 3. Fig. 2 is a flow diagram of the production method according to the present embodiment. Fig. 3 is a schematic diagram showing an example of a production process flow. Referring to Fig. 2, the production method according to the present embodiment includes a preparation step (#5), a moisture adjustment step (#10), an agglomeration step (#15), a water immersion step (#20), and a standing step (#25). In the production method according to the present embodiment, the moisture of the powdery ore 14 prepared in the preparation step (#5) is adjusted in the moisture adjustment step (#10), and then the powdery ore is compressed and agglomerated in the agglomeration step (#15) to form an agglomerate 16. The agglomerate 16 is subjected to a water immersion treatment and a standing treatment in the water immersion step (#20) and a standing step (#25). In the standing step (#25), a part of the metallic iron in the powdery ore 14 is oxidized and bonded, and a part or all of the calcium oxide-containing compounds in the powdery ore 14 are carbonated, thereby increasing the strength of the resulting carbon-containing agglomerate 21. Each step will be specifically described below with reference to FIG. 3.
[0049] [Preparation process (#5)] In the preparation step (#5), a powdery material 14 that is the raw material for the carbon-containing agglomerated ore 21 is prepared. The powdery material 14 contains metallic iron and a calcium oxide-containing compound. In this embodiment, the powdery material 14 is produced in the following procedure. With reference to FIG. 3, first, a carbonaceous material 2 (e.g., coke and anthracite) and a calcium-containing material 3 (e.g., lime) are added to an iron-based waste material 1. The iron-based waste material 1, the carbonaceous material 2, and the calcium-containing material 3 are transported to a mixer 5 by a belt conveyer 4, and mixed in the mixer 5 to obtain a mixed raw material 6.
[0050] The iron-based waste material 1 contains zinc and iron oxide, and is typically blast furnace dust, steelmaking dust, electric furnace dust, and the like. The iron-based waste material 1 or carbonaceous material 2 contains silicon-containing materials such as silicon dioxide and aluminum-containing materials such as aluminum oxide. In the example of this embodiment, the calcium-containing material 3 is milk of lime, which is a slurry-like material in which lime powder with a -0.2 mm ratio of 80% or more is suspended in water. "80% or more of -0.2 mm ratio" means that in the particle size distribution (cumulative distribution) of the lime powder, the mass ratio of particles with a particle size smaller than 0.2 mm to the total particles is 80% or more. Since milk of lime is extremely fine, it is highly reactive. The calcium-containing material 3 also contains calcium oxide. Lime powder may also be used as the calcium-containing material 3. The lime powder is a sieve-undersized product when obtaining lump-shaped limestone using a sieving device. The lime powder may be used as the calcium-containing material 3 as it is, or may be crushed to fine particles before being used as the calcium-containing material 3. By being crushed to fine particles, the calcium-containing material 3 is promoted to come into contact with the silicon-containing material and aluminum-containing material contained in the iron-based waste material 1 and the carbonaceous material 2, and the production of calcium silicate and calcium aluminate in a reduction furnace described later is facilitated.
[0051] Inside the integrated steelworks, blast furnace dust and steelmaking dust are generated, and outside the integrated steelworks, dust (e.g., electric furnace dust) is generated, which is transported into the integrated steelworks. Hereinafter, the dust generated inside the integrated steelworks may be referred to as iron-based waste 1a, and the dust generated outside may be referred to as iron-based waste 1b. When treating the iron-based waste 1 (iron-based waste 1a and iron-based waste 1b) in the integrated steelworks, the iron-based waste 1a and the calcium-containing material 3 may be mixed before being fed into the mixing device 5. In this case, the iron-based waste 1a and the calcium-containing material 3 (milk of lime) are fed into an adjustment tank (thickener) not shown, and mixed in the adjustment tank. Thereafter, the mixture of the iron-based waste 1a and the calcium-containing material 3 is dehydrated by a filter press not shown, and is fed to the mixing device 5. At this time, the iron-based waste 1b and the carbonaceous material 2 are also fed to the mixing device 5. The mixture of iron-based waste material 1a and calcium-containing material 3 is mixed with iron-based waste material 1b and carbonaceous material 2 in a mixing device 5, and is granulated into pellets to generate a mixed raw material 6. If there are no problems with the equipment, iron-based waste material 1b can also be mixed together with iron-based waste material 1a and calcium-containing material 3 (lime milk) in an adjustment tank (thickener).
[0052] Next, in the preparation step (#5), the mixed raw material 6 is charged into a reduction furnace, and the mixed raw material 6 is subjected to a reduction roasting treatment. In this embodiment, a rotary kiln 7 is used as the reduction furnace. The rotary kiln 7 is a rotating cylindrical type with a slight inclination. The mixed raw material 6 is charged from the inlet end 7a of the rotary kiln 7, and moves to the outlet end 7b of the rotary kiln 7 while performing a rolling motion within the rotary kiln 7. When the rotary kiln 7 is used as the reduction furnace, the particle size of the charged mixed raw material 6 may be small. The iron-based scrap 1 contains zinc and iron oxide, and by reducing the particle size of the mixed raw material 6, the dezincing treatment and the reduction of the iron oxide are promoted.
[0053] Air and fuel gas (e.g., coke oven gas) for thermal compensation and the like are supplied appropriately from the outlet end 7b of the rotary kiln 7. Within the rotary kiln 7, part of the carbonaceous material 2 is partially combusted by the fuel gas, generating carbon monoxide gas. This partial combustion that generates carbon monoxide gas maintains the temperature and atmosphere inside the rotary kiln 7 at a level necessary for reduction. The air and fuel gas supplied from the outlet end 7b flow in the opposite direction to the mixed raw material 6, and are discharged as exhaust gas from the inlet end 7a.
[0054] During the reduction roasting process, zinc contained in the iron-based scrap 1 is reduced and volatilized in the rotary kiln 7 and discharged together with the exhaust gas. A part of the iron oxide contained in the mixed raw material 6 (iron-based scrap 1) is reduced by the carbon monoxide gas contained in the rotary kiln 7 and becomes metallic iron. As a result, the mixed raw material 6 becomes reduced iron 8 containing metallic iron.
[0055] The mass ratio of metallic iron to the iron content contained in the reduced iron 8, that is, the metallization rate of iron, is typically 0.8 or less. If the content of metallic iron contained in the powdered and granular material 14 is increased, it becomes easier to obtain a high-strength carbon-containing agglomerate 21 even if a raw material containing carbon is used. From the viewpoint of use in a blast furnace, it is desirable that the metallization rate of iron is high. However, a huge amount of energy is required to obtain reduced iron 8 with a high metallization rate. In addition, when trying to obtain reduced iron 8 with a high metallization rate, there is a risk of problems such as sticking, in which the reduced iron 8 adheres to each other. Naturally, it is not easy to increase the content of metallic iron contained in the undersize product 12 described later. The undersize product 12 is obtained by classifying the reduced iron 8 with a movable sieve classifier 10 described later. For this reason, it is practical to set the metallization rate of the reduced iron 8 produced by the reduction roasting process to 0.8 or less. Furthermore, when iron-based waste material 1 such as dust is used as the raw material for reduced iron 8, the iron grade (total iron content) is low because it contains more impurities than when iron ore or the like is used as the raw material. The total iron content increases as oxygen is removed from the iron oxide contained in the iron-based waste material 1 as the reduction proceeds. However, even after the reduction roasting process, the total iron content of reduced iron 8 made of iron-based waste material 1 rarely exceeds 80 mass%. As such, since the total iron content itself in reduced iron 8 is low, it becomes even more difficult to obtain a powdered or granular material with a high metallic iron content even if a high metallization rate is obtained.
[0056] In the preparation step (#5), after the reduction roasting treatment, the reduced iron 8 is cooled in a cooling device 9. The method for cooling the reduced iron 8 is not particularly limited, but may be, for example, air cooling or water cooling. When the reduced iron 8 is cooled by air cooling, the reduced iron 8 after cooling contains almost no moisture.
[0057] Here, when powdered raw materials for blast furnace are charged into the blast furnace, troubles are likely to occur. Therefore, the powdered raw materials need to be agglomerated before being charged into the blast furnace. Therefore, in the preparation step (#5), the reduced iron 8 is first classified. Specifically, the cooled reduced iron 8 is put into a movable sieve classifier 10. In the example of this embodiment, the movable sieve classifier 10 is a vibrating sieve device. The movable sieve classifier 10 has a mesh net. Thereby, the reduced iron 8 is classified into agglomerated material 11, which is an oversize product, and a powdery undersize product 12. The mesh size of the movable sieve classifier 10 is, for example, 4 to 8 mm. The agglomerated material 11 has a sufficient size, so it is used as it is as raw materials for blast furnace. The undersize product 12 does not have a sufficient size, so it is compressed and agglomerated in the agglomeration step (#15) described later.
[0058] The sieve classifier used for classification in the preparation step (#5) must be a device capable of vibrating or rolling the reduced iron 8 (e.g., a vibrating sieve device). This is because the difference between the particle size of the lumpy material 11 and the particle size of the undersize product 12 is not that significant. If the reduced iron 8 is classified without vibrating or rolling, the undersize product 12, which has a particle size slightly smaller than the mesh size of the sieve classifier, may be mixed into the lumpy material 11 as the oversize product. In the preparation step (#5), the movable sieve classifier 10 is used as the sieve classifier, so that the undersize product 12 can be prevented from being mixed into the lumpy material 11. Therefore, if the carbon-containing agglomerated ore 21 obtained by the manufacturing method according to this embodiment is charged into a blast furnace, troubles are unlikely to occur and the operation of the blast furnace is stable.
[0059] A carbon-containing material 13 may be added to the undersize product 12. In the example of this embodiment, the undersize product 12 is fed into a mixer 15, and then the carbon-containing material 13 is added to the undersize product 12. This results in a powdered or granular material 14. The powdered or granular material 14 has a carbon content of 2.5% by mass or more. In other words, the carbon-containing material 13 is added to the undersize product 12 so that the carbon content is 2.5% by mass or more. However, if the undersize product 12 contains a sufficient amount of carbon, the undersize product 12 may be treated as the powdered or granular material 14 as it is without adding the carbon-containing material 13. The carbon-containing material 13 is, for example, coke powder or steel dust. The coke powder or steel dust may be used as the carbon-containing material 13 as it is, or the undersize product may be used as the carbon-containing material 13 after being classified by the above-mentioned movable sieve classifier 10. Iron and steel dust is dust generated during the steelmaking process, and is primarily composed of iron oxide and carbon, as shown in Table 5 below.
[0060] In the example of this embodiment, the powdered or granular material 14 (and the lump material 11) contains calcium silicate (e.g., di-calcium silicate). Di-calcium silicate is produced by mixing a calcium-containing material 3 (e.g., calcium carbonate, calcium hydroxide, calcium oxide, etc.) with a silicon-containing material (fine silicate, clay, silica fume, fly ash, amorphous silica, etc.) and firing it. There are α-type, α'-type, β-type, and γ-type di-calcium silicate. In the example of this embodiment, a silicon-containing material such as silicon dioxide contained in the mixed raw material 6 reacts with the calcium-containing material 3 to produce calcium silicate. However, the powdered or granular material 14 may contain calcium aluminate instead of calcium silicate, or may contain both calcium silicate and calcium aluminate. An aluminum-containing material such as aluminum oxide reacts with the calcium-containing material 3 to produce calcium aluminate. The aluminum-containing material is contained in, for example, the iron-based scrap material 1. Calcium silicate and calcium aluminate are produced, for example, during reduction roasting treatment. Calcium silicate and calcium aluminate are components contained in cement, and both harden by carbonation.
[0061] In the manufacturing method of this embodiment, calcium silicate contained in the powdery ore 14 is carbonated in the water immersion step (#20) and the standing step (#25) described later. Calcium silicate is also a strength-imparting component contained in cement, and the strength of the carbon-containing agglomerates 21 manufactured using this powdery ore 14 is greater than the strength of the carbon-containing agglomerates 21 manufactured using the powdery ore 14 that does not contain calcium silicate.
[0062] Calcium silicate is also contained in, for example, high silicon-based binders (e.g., Portland cement). Therefore, in order to improve the strength of the carbon-containing agglomerated ore 21, a high silicon-based binder may be added to the powdered ore 14. However, the high silicon-based binder contains silicon-containing substances such as silicon dioxide, and also usually contains aluminum-containing substances such as aluminum oxide. Silicon-containing substances are unnecessary components in the iron-making process. Furthermore, aluminum-containing substances are components that destabilize the operation of a blast furnace. Adding a high silicon-based binder to the powdered ore 14 increases the content of silicon-containing substances and aluminum-containing substances in the powdered ore 14. If the powdered ore 14 to which a high silicon-based binder has been added is used as a raw material for a blast furnace, the amount of silicon-containing substances and aluminum-containing substances, which are unnecessary components in the iron-making process, charged into the blast furnace will increase. Furthermore, when the high silicon-based binder is added to the powdered granular material 14, the powdered granular material 14 and the high silicon-based binder need to be mixed as uniformly as possible. In order to mix the powdered granular material 14 and the high silicon-based binder uniformly, a high-performance mixing device is required. When the high silicon-based binder is added to the powdered granular material 14, the cost of preparing and mixing the high silicon-based binder increases compared to when the high silicon-based binder is not added. For the above reasons, it is preferable that the high silicon-based binder is not added to the powdered granular material 14 as much as possible. The content of the high silicon-based binder in the powdered granular material 14 on a dry basis is preferably 2 mass% or less. More preferably, the high silicon-based binder is not added to the powdered granular material 14. The dry basis refers to a state in which the powdered granular material 14 does not contain moisture, that is, a state in which the moisture in the powdered granular material 14 is zero.
[0063] The iron-based scrap material 1 and carbonaceous material 2 from which the powdery material 14 is derived also contain silicon-containing and aluminum-containing substances, but it is not easy to separate and remove them, and it is unavoidable to feed them into a blast furnace. However, calcium silicate and calcium aluminate obtained by reacting the silicon-containing and aluminum-containing substances contained in the iron-based scrap material 1 and carbonaceous material 2 with the calcium-containing substance 3 are effective components from the viewpoint of ensuring crushing strength. There is no need to intentionally increase the amount of silicon-containing and aluminum-containing substances fed into the blast furnace, which are unnecessary components in the steelmaking process. Therefore, in the manufacturing method of this embodiment, it is considered that the silicon-containing and aluminum-containing substances contained in the iron-based scrap material 1 and carbonaceous material 2, which are raw materials in the rotary kiln 7, and which are impurities in the steelmaking process, are converted into calcium silicate and calcium aluminate, which contribute to the development of strength. According to the manufacturing method of this embodiment, calcium silicate and calcium aluminate are produced as by-products from silicon-containing substances and aluminum-containing substances that are contained in raw materials such as the iron-based waste material 1 and are impurities in the iron-making process during the reducing roasting process, and are included in the powdery and granular substance 14, making it possible to omit the addition of a high silicon-based binder to the powdery and granular substance 14. In addition, the metallic iron produced in the reducing roasting process also has the same function as the high silicon-based binder.
[0064] In the reduction roasting process, the temperature conditions in the reduction furnace are not particularly limited. It is generally known that the temperature at which the raw material is fired to produce dicalcium silicate is preferably 1300°C or higher, more preferably 1400°C or higher. At temperatures below 1300°C, the fired raw material may be undercooked.
[0065] However, in this embodiment, the calcium-containing material 3 is a slurry of milk of lime. This increases the contact efficiency of the calcium-containing material 3 and the silicon-containing material contained in the mixed raw material 6. Therefore, by using such a mixed raw material 6, the reactivity of the calcium-containing material 3 with the silicon-containing material is improved, and di-calcium silicate is produced even under a temperature condition of less than 1300°C. If the reduction roasting treatment temperature can be set to less than 1300°C, excessive production of low-melting-point substances adhering to the inner wall of the rotary kiln 7 is suppressed, and the growth of the deposits on the inner wall of the rotary kiln 7 is suppressed. Furthermore, lowering the reduction roasting treatment temperature leads to a reduction in the amount of fuel used in the rotary kiln operation, an improvement in the life of the refractories in the rotary kiln, and a reduction in the load on the equipment.
[0066] The powdered or granular material 14 has a total iron content of 10 mass% or more, a carbon content of 2.5 mass% or more, and a mass ratio of the total amount of calcium to the total amount of silicon of 2.9 to 6.1 on a dry basis. Furthermore, in the powdered or granular material 14, the metallic iron content a, the calcium oxide content b, and the carbon content c satisfy the above formula (1). In the preparation step (#5), the amounts of each raw material to be used and the reduction conditions in the rotary kiln 7 are determined so as to satisfy these requirements.
[0067] The right side of formula (1) corresponds to the crushing strength of the carbon-containing agglomerates 21 obtained by the manufacturing method of this embodiment. Therefore, formula (1) means that the crushing strength of the carbon-containing agglomerates 21 is 400 N / piece or more. Raw materials charged into a blast furnace are required to have high strength to ensure gas permeability inside the furnace. The crushing strength of the carbon-containing agglomerates 21 needs to be 400 N / piece or more. Preferably, the crushing strength is 980 N / piece or more.
[0068] Preferred ranges for the metallic iron content a and calcium oxide content b of the powdered or granular material 14, and the mass ratio of the calcium-containing material 3 and the silicon-containing material contained in the mixed raw material 6 will be described below.
[0069] It is preferable that the powdery or granular material 14 contains a sufficient amount of metallic iron. This is because the oxidation bond of the metallic iron in the powdery or granular material 14 is promoted in the standing step (#25), and the strength of the obtained carbon-containing agglomerated ore 21 can be more reliably ensured. The metallic iron content a of the powdery or granular material 14 is preferably 10 mass% or more.
[0070] Similarly, it is preferable that the powdery granular material 14 contains a sufficient amount of calcium oxide-containing compound. This is because the carbonation of the calcium oxide-containing compound in the powdery granular material 14 is promoted in the settling step (#25), and the strength of the resulting carbon-containing agglomerated ore 21 can be more reliably ensured. Furthermore, the calcium oxide-containing compound is also a component used to adjust the basicity of molten slag in the iron-making process. Therefore, the powdery granular material 14 needs to contain a certain amount of calcium oxide. However, if the powdery granular material 14 contains an excessive amount of calcium oxide-containing compound, the amount of material to be processed increases in the reduction roasting process and the agglomeration process in the agglomeration step (#15) described later, and the production efficiency decreases. Naturally, the more the amount of the calcium oxide-containing compound contained in the powdery granular material 14, the higher the calcium oxide content b of the powdery granular material 14. The calcium oxide content b of the powdery granular material 14 is preferably 10% by mass or more and 40% by mass or less.
[0071] Dicalcium silicate is a compound with a calcium to silicon mass ratio of 2.9. The calcium to silicon mass ratio means the calcium content (mass%) relative to the silicon content (mass%). Therefore, if the calcium to silicon mass ratio contained in the mixed raw material 6 is 2.9 or more, dicalcium silicate is easily produced. In addition, in this case, when the mixed raw material 6 is subjected to a reduction roasting treatment using the rotary kiln 7, the production of low melting point substances adhering to the inner wall of the rotary kiln 7 is suppressed, and excessive growth of the deposits on the inner wall of the rotary kiln 7 is suppressed. However, if the calcium to silicon mass ratio is too large, the amount of the object to be treated increases in the reduction roasting treatment and the agglomeration treatment in the agglomeration step (#15) described later, and the production efficiency decreases. Therefore, in the example of this embodiment, the calcium to silicon mass ratio contained in the mixed raw material 6 is 2.9 or more and 6.1 or less. As described above, the mass ratio of calcium to silicon contained in the powdered or granular material 14 obtained from the mixed raw material 6 is also 2.9 or more and 6.1 or less.
[0072] [Moisture adjustment process (#10)] In the moisture adjustment step (#10), water is added to the powdered granular material 14 to adjust the moisture content of the powdered granular material 14. In the example of this embodiment, water is added to the powdered granular material 14 in the mixer 15. If the powdered granular material 14 contains an appropriate amount of moisture, a high-strength agglomerated material 16 is likely to be obtained when the powdered granular material 14 is agglomerated in the agglomeration step (#15) described below. This is because frictional resistance between particles of the powdered granular material 14 is reduced, making it easier for compression force to be transmitted, and promoting consolidation of the powdered granular material 14. In addition, when a double-roll briquette molding machine is used as the agglomeration device 17 for agglomerating the powdered granular material 14, if the powdered granular material 14 contains an appropriate amount of moisture, frictional resistance between the powdered granular material 14 and the roll surface is reduced, and the life of the roll is improved.
[0073] The powdery and granular material 14 contains metallic iron and di-calcium silicate. The water added to the powdery and granular material 14 also contributes to the oxidation of metallic iron and the carbonation of di-calcium silicate. If the oxidation of metallic iron and the carbonation of di-calcium silicate are promoted, the strength of the finally obtained carbon-containing agglomerated ore 21 is increased. For the above reasons, it is preferable that the moisture content of the powdery and granular material 14 is relatively high. Therefore, in the moisture adjustment step (#10), the moisture content of the powdery and granular material 14 is adjusted to 0.5 mass% or more.
[0074] On the other hand, if the powdered granular material 14 contains a large amount of moisture, it may be difficult to agglomerate the powdered granular material 14 in the agglomeration step (#15). If the powdered granular material 14 contains excessive moisture, the powdered granular material 14 may adhere to the rolls of the agglomeration device 17 (double-roll briquette molding machine). In this case, the powdered granular material 14 may hang off the hopper for supplying the powdered granular material 14 to the agglomeration device 17, which may cause the supply of raw material to the agglomeration device 17 to become unstable. For this reason, in the moisture adjustment step (#10), the moisture content of the powdered granular material 14 is adjusted to 7.0 mass % or less. This allows the powdered granular material 14 to be stably agglomerated in the agglomeration step (#15).
[0075] In the moisture adjustment step (#10), it is also possible to further add oil and lubricants to the powdery or granular material 14. In this case, however, when the agglomerates 16 are subjected to water immersion and static treatment in the water immersion step (#20) and static treatment in the static setting step (#25) described below, the oil contained in the oil and lubricants may be mixed into wastewater or soil, causing environmental problems. Therefore, it is preferable that oil and lubricants are not added to the powdery or granular material 14.
[0076] In this embodiment, before water is added to the powdered or granular material 14 in the moisture adjustment step (#10), the reduced iron 8 is classified by a movable sieve classifier 10 such as a vibrating sieve device in the preparation step (#5). That is, the classification of the reduced iron 8 is performed in a dry state. In this case, the reduced iron 8 is less likely to adhere to the mesh net of the movable sieve classifier.
[0077] [Agglomeration process (#15)] In the agglomeration step (#15), after the moisture adjustment step (#10), the powdery material 14 is cold compressed and agglomerated to form an agglomerate 16. An agglomeration device 17 is used for the compression and agglomeration. In general, methods for compressing and agglomerating powdery material are roughly divided into tabletting and roll pressing. In tabletting, a powdery material is filled in a closed mold, and the filled powdery material is compressed by a piston to be molded into a predetermined shape. Roll pressing includes briquetting. In briquetting, an agglomeration device having two rotatable rolls is used. The agglomeration device 17 used in the manufacturing method of this embodiment is a double-roll briquette molding machine. In short, in the example of this embodiment, the powdery material 14 is compressed and agglomerated by briquetting.
[0078] FIG. 4 is a cross-sectional view of the agglomeration device 17 used in the manufacturing method of this embodiment. Referring to FIG. 4, the agglomeration device 17 includes two cylindrical rolls 171, 172. The rolls 171 and 172 are adjacent to each other with a horizontal gap therebetween. A hopper (not shown) is provided above the two rolls 171, 172. The powdered or granular material 14 after the moisture adjusting step (#10) is supplied from the hopper toward the gap between the two rolls 171, 172. The two rolls 171, 172 rotate in a direction approaching each other from above. A plurality of pockets 171a, 172a are provided on the outer surfaces of the rolls 171, 172 along the circumferential direction. It can also be said that each of the rolls 171, 172 has a plurality of recesses. The pockets 171a, 172a become a mold for forming the powdered or granular material 14 into the agglomerated product 16. That is, a part of the shape of the obtained agglomerates 16 substantially coincides with the shapes of the pockets 171a, 172a.
[0079] In the agglomeration step (#15), the powdered granular material 14 is supplied between the two rotating rolls 171, 172, and the powdered granular material 14 is compressed while slipping due to friction between the surfaces of the rolls 171, 172 and the powdered granular material 14. At that time, the powdered granular material 14 is compressed by the two rolls 171, 172, and the particles of the powdered granular material 14 approach each other. Therefore, an agglomerate 16 having few voids and high density is obtained. Furthermore, since the powdered granular material 14 is compressed by the rotation of the rolls 171, 172, the strength of the obtained agglomerate 16 is greater than that of the agglomerate obtained by tableting. In addition, the operation of the double-roll briquette molding machine is continuous and highly productive. From the above, the method of compressing and agglomerating the powdered granular material 14 to form the agglomerate 16 is preferably briquetting, and a double-roll briquette molding machine is preferably used.
[0080] It is more preferable that the agglomerating device 17 is configured to be capable of automatically controlling the molding pressure when compressing the powdered or granular material 14 with the rolls 171, 172. The molding pressure is important from the viewpoint of controlling the moldability and crushing strength of the agglomerates 16. The required molding pressure varies depending on the properties of the powdered or granular material 14 and the amount of powdered or granular material 14 stored in the hopper. If the agglomerating device 17 is a double-roll briquette molding machine capable of automatically controlling the molding pressure, the molding pressure can be controlled to be close to a target value, and the quality of the obtained agglomerates 16, such as the crushing strength, can be stabilized.
[0081] However, even if the powdery granular material 14 is compressed and agglomerated by the agglomerating device 17, a portion of the powdery granular material 14 may not be agglomerated and remain as the powdery granular material 14. In the agglomerating step (#15), the compressed agglomerates 16 and the remaining powdery granular material 14 are passed through a sieve classifier 18. The sieve classifier 18 has a mesh net. As a result, the mixture of the agglomerates 16 and the powdery granular material 14 is classified into the agglomerates 16, which are oversize products, and the powdery granular material 14, which is undersize products. As shown in FIG. 3, the powdery granular material 14, which is undersize products, is returned to a stage prior to the mixer 15 and supplied to the agglomerating device 17 to be compressed and agglomerated again. The particle size of the undersize product (powdery material 14) in the agglomeration step (#15) may be finer than the particle size of the powdery material 14 after the preparation step (#5) and moisture adjustment step (#10). Therefore, the undersize product in the agglomeration step (#15) is mixed with the powdery material 14 after the preparation step (#5) and moisture adjustment step (#10). This increases the packing density when the powdery material 14 is compressed into agglomerates using the agglomeration device 17. This makes it easier to obtain agglomerates 16 with high crushing strength.
[0082] The difference between the particle size of the agglomerates 16 and the particle size of the powdery material 14 is significant. Therefore, the sieve classifier 18 may be a movable sieve classifier such as a vibrating sieve device, or may not be. When a movable sieve classifier is not used, a mesh net with a predetermined mesh size is installed at an angle, and the mixture of the agglomerates 16 and the powdery material 14 is rolled on the mesh. If the mesh of the sieve classifier 18 is made large enough that the agglomerates 16 do not pass through, it is considered that the powdery material 14 will surely pass through the mesh even if the mixture of the agglomerates 16 and the powdery material 14 is not vibrated. The mesh of the sieve classifier 18 may be larger than the mesh of the movable sieve classifier 10. The mesh size of the sieve classifier 18 is, for example, 10 to 15 mm.
[0083] When the mesh of the sieve classifier 18 is larger than the mesh of the movable sieve classifier 10, the undersize product (the powdery material 14) after classification by the sieve classifier 18 may contain particles larger than the mesh of the movable sieve classifier 10. When such large particles are compressed and agglomerated by the agglomeration device 17, an excessive load is applied to the agglomeration device 17. Therefore, when the mesh of the sieve classifier 18 is larger than the mesh of the movable sieve classifier 10, the powdery material 14 after classification by the sieve classifier 18 is returned to a stage before the movable sieve classifier 10. When the powdery material 14 after classification by the sieve classifier 18 is further classified by the movable sieve classifier 10, the particles larger than the mesh of the movable sieve classifier 10 are removed from the powdery material 14 as agglomerated material 11.
[0084] [Water immersion process (#20)] In the water immersion step (#20), the agglomerates 16 after classification by the sieve classifier 18 are subjected to a water immersion treatment. In the example of this embodiment, in the water immersion step (#20), the agglomerates 16 are fed into a water immersion treatment device 19 filled with water 20. The water immersion treatment means that the entire surface of the agglomerates 16 is kept in contact with the water 20 for a predetermined period of time. However, when multiple agglomerates 16 are fed into the water immersion treatment device 19, it is sufficient that the surfaces of the agglomerates 16, excluding the portions where the agglomerates 16 are in contact with each other, are in contact with the water 20.
[0085] The water immersion treatment may be carried out immediately after the production of the agglomerates 16, or may be carried out several hours or more after the production of the agglomerates 16. However, the strength of the agglomerates 16 increases when they are left to stand after production. The agglomerates 16 with increased strength are less likely to be damaged even if they are subjected to a drop impact or the like during the transportation of the agglomerates 16. Therefore, in the water immersion step (#20), the agglomerates 16 are preferably left to stand for 15 to 20 minutes or more after production, and then the water immersion treatment is carried out.
[0086] The time for which the agglomerates 16 are subjected to the water immersion treatment is not particularly limited and may be set appropriately depending on the material, size, etc. of the agglomerates 16. However, from the viewpoint of allowing the water 20 to sufficiently penetrate the agglomerates 16, the time for which the water immersion treatment is performed is preferably 3 seconds or more. If the time for which the water immersion treatment is performed is too long, the productivity deteriorates. Therefore, the time for which the agglomerates 16 are subjected to the water immersion treatment is preferably 3 seconds or more and 600 seconds or less.
[0087] The agglomerates 16 after classification by the sieve classifier 18 may be placed in a storage container filled with water 20 and subjected to a water immersion treatment in this storage container. In other words, storage of the agglomerates 16 and a water immersion treatment may be performed simultaneously. In this case, the time for which the agglomerates 16 are subjected to the water immersion treatment may be longer than 600 seconds. This is because there is no substantial problem from the viewpoint of ensuring the strength of the agglomerates 16.
[0088] The water 20 used in the water immersion treatment may be, for example, tap water, industrial water, seawater, or industrial wastewater. The pH of the water 20 may be lower than 7, since the oxidation of the metallic iron contained in the agglomerates 16 is promoted and the strength of the agglomerates 16 is improved. The Iron and Steel Institute of Japan, Materials and Processes (CAMP-ISIJ), vol. 25 (2012), p. 279, describes that the crushing strength of the carbon-containing agglomerates 21 obtained by the water immersion treatment using a sodium chloride aqueous solution is higher than that obtained by the water immersion treatment using pure water. When a sodium chloride aqueous solution is used in the water immersion treatment, it is expected that the processing time of the static treatment performed after the water immersion treatment can be shortened. In that case, it is necessary to consider the corrosion of the equipment caused by using the sodium chloride aqueous solution. However, from the viewpoint of ensuring the strength required as a raw material for a blast furnace, there is no practical problem even if the water 20 having a pH higher than 7 is used in the water immersion treatment. The required crushing strength can be obtained by lengthening the static treatment time. Therefore, inexpensive industrial wastewater having a pH higher than 7 may be used as the water 20.
[0089] [Standing process (#25)] In the still standing step (#25), after the water immersion step (#20), the agglomerates 16 are subjected to a still standing treatment. Specifically, in the still standing step (#25), the agglomerates 16 after the water immersion treatment are left standing in an atmosphere containing oxygen and carbon dioxide. The agglomerates 16 after the still standing treatment become carbon-containing agglomerates 21.
[0090] The agglomerates 16 are obtained by agglomerating the powdery and granular material 14, and therefore contain metallic iron and calcium oxide-containing compounds such as calcium silicate, just like the powdery and granular material 14. In the water immersion step (#20), the agglomerates 16 are immersed in water, and water 20 enters the open pores of the agglomerates 16. Thereafter, in the standing step (#25), the agglomerates 16 are left standing, so that the metallic iron and calcium oxide-containing compounds in the vicinity of the open pores dissolve in the water 20 that has entered the open pores. Oxygen and carbon dioxide in the atmosphere also dissolve in the water 20. By leaving the agglomerates 16 standing in this state, the agglomerates 16 are dehydrated, and oxidation of part of the metallic iron and carbonation of the calcium oxide-containing compounds (calcium silicate, etc.) proceed. Specifically, oxidation of the metallic iron that has dissolved in the water 20 proceeds due to oxygen in the atmosphere. Carbonation of the calcium oxide-containing compound (calcium silicate, etc.) dissolved in the water 20 by carbon dioxide in the atmosphere (for convenience of explanation, hereinafter, these carbonations are collectively referred to as "carbonation of calcium oxide-containing compound") progresses. As a result, iron oxide and calcium carbonate are generated in the agglomerates 16 at the positions where the open pores were present. Calcium carbonate is a type of calcium oxide-containing compound. Although the calcium carbonate contained in the powdery granular material 14 before the water immersion treatment is an already carbonated compound, it enters the open pores of the agglomerates 16 and contributes to the development of strength as a filler. For example, when carbon dioxide gas in the atmosphere is absorbed by the water 20 that has entered the open pores, the calcium carbonate in the vicinity of the open pores becomes easily dissolved in the water 20. The calcium carbonate dissolved in the water 20 remains in the open pores even after the water 20 evaporates in the subsequent static treatment, and fills the open pores together with calcium carbonate generated by the carbonation of other calcium oxide-containing compounds, enhancing the bonding force between the substances in the vicinity of the open pores and contributing to the development of strength of the agglomerates 16. In this way, calcium carbonate and iron oxide bond the particles around the open pores of the agglomerates 16 together and strengthen the bond, thereby improving the strength of the resulting carbon-containing agglomerates 21.
[0091] Carbonation of the calcium oxide-containing compound contained in the left agglomerates 16 proceeds even in an atmosphere with a carbon dioxide concentration of less than 1%. Therefore, the agglomerates 16 may be left in the air in an outdoor yard. The period for leaving the agglomerates 16 is not particularly limited, but is, for example, 3 to 10 days.
[0092] During the standing treatment, when the water 20 absorbed in the agglomerates 16 during the water immersion treatment runs out, the oxidation of the metallic iron and the carbonation of the calcium oxide-containing compounds stop at that point. Therefore, if the standing treatment is performed in an outdoor yard, rain will supply water to the agglomerates 16, which will promote the oxidation of the metallic iron and the carbonation of the calcium oxide-containing compounds in the subsequent standing treatment, thereby increasing the crushing strength of the agglomerates 16. Furthermore, in the standing step (#25), water may be sprayed on the agglomerates 16 during the standing treatment.
[0093] The atmospheric temperature during the standing treatment is not particularly limited. However, if the atmospheric temperature is less than 5°C, the oxidation of metallic iron and the carbonation reaction of calcium oxide-containing compounds are difficult to proceed. In that case, measures such as extending the standing treatment time are required, and productivity is deteriorated. On the other hand, if the atmospheric temperature during the standing treatment is set to 5°C or higher, preferably 15°C or higher, the oxidation of metallic iron and the carbonation reaction of calcium oxide-containing compounds can be promoted, and productivity is improved. On the other hand, if the atmospheric temperature exceeds 50°C, the evaporation of the water 20 absorbed into the agglomerates 16 during the water immersion treatment becomes faster, and there is a concern that the water will disappear from the agglomerates before sufficient strength is obtained. It can also be said that if the atmospheric temperature during the standing treatment is set to 50°C or lower, the instant evaporation of the water 20 from the agglomerates 16 can be suppressed. For the above reasons, the atmospheric temperature during the standing treatment is set to 5°C or higher and 50°C or lower, preferably 15°C or higher and 50°C or higher.
[0094] In the still-standing step (#25), the still-standing treatment may be performed using a still-standing treatment device (not shown). In this case, the agglomerates 16 are left still in the still-standing treatment device. In the still-standing treatment device, the temperature, humidity, oxygen concentration, and carbon dioxide gas concentration of the atmosphere are controlled. The still-standing treatment may be performed in an atmosphere in which the carbon dioxide gas concentration is controlled to be higher than that in the air. If the still-standing treatment is performed in an atmosphere containing carbon dioxide gas, carbonation of the calcium oxide-containing compound in the agglomerates 16 is promoted. This improves the strength of the obtained carbon-containing agglomerates 21. In addition, the strength development speed is increased, and the still-standing treatment time is shortened.
[0095] The mass of each of the carbon-containing agglomerates 21 produced by the production method according to the present embodiment is preferably large. This is because productivity is increased. However, if the mass is too large, the impact of dropping the carbon-containing agglomerates 21 during transportation and conveyance is large, and the carbon-containing agglomerates 21 are likely to be damaged. In addition, the carbon-containing agglomerates 21 may be used in electric furnaces other than blast furnaces. If the mass of each of the carbon-containing agglomerates 21 is large, the volume of the carbon-containing agglomerates 21 also becomes large. If the volume of the carbon-containing agglomerates 21 becomes too large, the heat transfer in the electric furnace is deteriorated, and it becomes difficult to melt them efficiently. For this reason, the weight of each of the agglomerates 16 after the settling step (#25) is preferably 40 g or less, more preferably 30 g or less.
[0096] [effect] In the manufacturing method according to the present embodiment, a powdery ore 14 containing carbon is prepared in the preparation step (#5). Specifically, the powdery ore 14 has a total iron content of 10 mass% or more, a carbon content of 2.5 mass% or more, and a ratio of the total amount of calcium to the total amount of silicon of 2.9 to 6.1 in mass ratio on a dry basis. By making the carbon content 2.5 mass% or more, when the manufactured carbon-containing agglomerated ore 21 is used in a blast furnace, the effects of reducing the fuel ratio and improving productivity are expected to be significant. However, by making the powdery ore 14 contain carbon, it becomes difficult to maintain the strength of the obtained carbon-containing agglomerated ore 21. Therefore, in the manufacturing method according to the present embodiment, the moisture contained in the powdery ore 14 is adjusted, and then the powdery ore 14 is compressed and agglomerated to manufacture the agglomerated material 16. Furthermore, the agglomerated material 16 is subjected to a water immersion treatment and a static treatment. The metallic iron contained in the powdery ore 14 is interlocked with and compressed and bonded due to its plasticity when compressed into agglomerates. Furthermore, by subjecting the manufactured agglomerates 16 to a water immersion and standing treatment, a part of the metallic iron is oxidized and bonded, and the strength of the obtained carbon-containing agglomerates 21 is increased. In other words, the metallic iron is used as a binder. Furthermore, by carbonating a part or all of the calcium oxide-containing compound in the powdery ore 14, it is possible to suppress a decrease in the strength of the manufactured carbon-containing agglomerates 21, even if a raw material containing carbon is used.
[0097] Furthermore, in the preparation step (#5), the metallic iron content a, calcium oxide content b, and carbon content c of the powdery and granular material 14 are adjusted to satisfy the above formula (1). The right side of formula (1) corresponds to the crushing strength of the carbon-containing agglomerates 21 when the powdery and granular material 14 is compressed and agglomerated, and the agglomerates 16 are subjected to water immersion and static treatment to produce the carbon-containing agglomerates 21. In other words, when the powdery and granular material 14 satisfying the above formula (1) is used as a raw material, the resulting carbon-containing agglomerates 21 have a crushing strength of 400 N / piece or more. Therefore, according to the manufacturing method of this embodiment, even when a raw material having a carbon content of 2.5 mass% or more is used, the carbon-containing agglomerates 21 having a strength usable in a blast furnace can be manufactured.
[0098] The agglomerates 16 absorb water 20 during the water immersion process and expand. In general, if the agglomerates expand excessively, they collapse. However, although the agglomerates 16 expand somewhat, they do not collapse due to bonding between metallic iron particles caused by pressure or biting. Generally, the agglomerates fed into the high temperature section of a blast furnace may collapse due to thermal expansion. However, even in this case, if the metallic iron particles contained in the agglomerates 16 are bonded to each other by pressure or biting, the collapse of the agglomerates 16 is suppressed. Therefore, in the manufacturing method according to the present embodiment, multiple factors such as the oxidative bonding of the metallic iron contained in the agglomerates 16 and the carbonation of the calcium oxide-containing compound described above act on the strength and shape of the agglomerates 16. The strength and shape of the agglomerates 16 are maintained by the synergistic effect of these factors. In other words, in order to maintain the strength and shape of the agglomerates 16, the agglomerates 16 need to contain a certain amount of metallic iron. In the present embodiment, the content rate a of metallic iron in the powdered or granular material 14, which is the raw material of the agglomerates 16, is 10 mass % or more, so that the strength and shape of the agglomerates 16 can be maintained.
[0099] [Variations] In the above-described embodiment, the reduction furnace used in the reduction roasting process is a rotary kiln 7. However, the reduction furnace may be a rotary hearth furnace, a fluidized bed furnace, a shaft furnace, or the like. When a rotary hearth furnace is used as the reduction furnace, the mixed iron-based waste material 1, the carbonaceous material 2, and the calcium-containing material 3 (mixed raw material 6) are agglomerated and then charged into the rotary hearth furnace. During the reduction roasting process, a part of the iron oxide is reduced in the rotary hearth furnace to become metallic iron. As a result, the mixed raw material 6 becomes reduced iron 8 containing metallic iron. Most of the reduced iron 8 obtained from the rotary hearth furnace is agglomerated. If the strength of the agglomerated reduced iron 8 is insufficient, the reduced iron 8 may be agglomerated again in the agglomerating device 17 in the agglomerating step (#15). In this case, the agglomerated reduced iron 8 may be crushed once in order to pass the reduced iron 8 through the agglomerating device 17.
[0100] In the above embodiment, the reduced iron 8 is classified by the movable sieve classifier 10 in the preparation step (#5). However, the classification of the reduced iron 8 by the movable sieve classifier 10 may be performed after the moisture adjustment step (#10). In this case, the reduced iron 8 is classified by the movable sieve classifier 10 after water is added in the moisture adjustment step (#10). A manufacturing process flow of the carbon-containing agglomerated ore 21 in this case is shown in FIG. 5. FIG. 5 is a schematic diagram showing an example of the manufacturing process flow. In the manufacturing process flow shown in FIG. 5, the reduced iron 8 cooled by the cooling device 9 is input into the mixer 15, and the carbon-containing material 13 is added. Then, water is added to the reduced iron 8 and the carbon-containing material 13 in the mixer 15, and moisture adjustment is performed. The reduced iron 8 and carbon-containing material 13 after the moisture adjustment are passed through a movable sieve classifier 10 and classified into a lump material 11 which is an over-sieve product and a powdery material 14 which is an under-sieve product.
[0101] If dry reduced iron 8 is classified using the movable sieve classifier 10, there is a risk that the reduced iron 8 may vibrate or generate dust. Therefore, if the reduced iron 8 after water has been added is classified using the movable sieve classifier 10, dust generation from the reduced iron 8 is suppressed. In the moisture adjustment step (#10), from the viewpoint of suppressing dust generation, it is preferable that the moisture content of the powdered or granular material 14 is adjusted to 0.5 mass % or more.
[0102] When the reduced iron 8 to which water has been added is classified using the movable sieve classifier 10, if excess moisture is added to the reduced iron 8, the reduced iron 8 is likely to adhere to the mesh screen of the movable sieve classifier 10. This reduces the efficiency of classification. Therefore, in the moisture adjustment step (#10), the moisture content of the reduced iron 8 is adjusted to 7.0 mass % or less. If the moisture content of the reduced iron 8 is 7.0 mass % or less, the reduced iron 8 is less likely to adhere to the mesh screen of the movable sieve classifier 10.
[0103] In the above embodiment, the reduced iron 8 produced in the rotary kiln 7 is classified into undersize fraction 12 by the movable sieve classifier 10. The carbon-containing material 13 is added to the undersize fraction 12 to obtain the powdered or granular material 14. The powdered or granular material 14 is compressed and agglomerated by the agglomerator 17 after water is added by the mixer 15. This process is carried out in a continuous facility. However, the reduced iron 8 and the powdered or granular material 14 may be temporarily stored during the process and the process may be resumed after a period of time. For example, even if the agglomerator 17 is stopped due to maintenance or a problem, the operation of the rotary kiln 7 may be continued. In this case, the reduced iron 8 produced in the rotary kiln 7 may be temporarily stored, and the reduced iron 8 (the powdered or granular material 14) may be compressed and agglomerated after the operation of the agglomerator 17 is resumed. Conversely, if the reduced iron 8 and the powdered material 14 are temporarily stored, the agglomeration by the agglomeration device 17 continues even if the rotary kiln 7 is stopped.
[0104] The reason why the reduced iron 8 and the powdered and granular material 14 can be temporarily stored is because the compression and agglomeration is performed in a cold state in the agglomeration step (#15) in the above embodiment. When the compression and agglomeration is performed in a hot state, the temperature of the reduced iron 8 produced in the rotary kiln 7 needs to be maintained at about 700°C. Therefore, when the compression and agglomeration is performed in a hot state, it is difficult to temporarily store the reduced iron 8 and the powdered and granular material 14.
[0105] In the moisture adjustment step (#10) of the above embodiment, water is added to the powdered or granular material 14 to adjust the moisture contained in the powdered or granular material 14. As described above, in the manufacturing process flow shown in FIG. 5, water may be added to the reduced iron 8 and the carbon-containing material 13 to adjust the moisture contained in the reduced iron 8 and the carbon-containing material 13. However, the method for adjusting the moisture contained in the powdered or granular material 14 or the reduced iron 8 (and the carbon-containing material 13) is not limited to this. A method for adjusting the moisture of the powdered or granular material 14 will be described below, but the moisture of the reduced iron 8 and the carbon-containing material 13 can also be adjusted using a similar method. Therefore, in the following description of moisture adjustment, "powdered or granular material 14" may be read as "reduced iron 8 and the carbon-containing material 13."
[0106] For example, the moisture content of the powdered or granular material 14 may be adjusted by mixing a powdered or granular material 14 containing moisture with a dry powdered or granular material 14. In other words, in the moisture adjustment step (#10), a powdered or granular material 14 containing moisture may be used as a moisture source instead of water. The powdered or granular material 14 containing moisture is, for example, a powdered or granular material 14 that has absorbed moisture when rain fell while it was temporarily stored in an outdoor yard, or a powdered or granular material 14 that has been produced in a rotary kiln 7 and then cooled by water cooling. The dry powdered or granular material 14 is, for example, a powdered or granular material 14 that has been produced in a rotary kiln 7 and then cooled by air cooling.
[0107] In the moisture adjustment step (#10), when the powdered or granular material 14 containing moisture is used as the moisture source, if the powdered or granular material 14 containing moisture and the dry powdered or granular material 14 are classified separately, two movable sieve classifiers 10 are required, which increases costs. In addition, in this case, if the powdered or granular material 14 containing moisture contains excess moisture, the powdered or granular material 14 containing moisture adheres to the mesh of the movable sieve classifier 10, which reduces the classification efficiency. On the other hand, if the dry powdered or granular material 14 is classified by the movable sieve classifier 10, the dry powdered or granular material 14 may generate dust. For these reasons, when the powdered or granular material 14 containing moisture is used as the moisture source, it is preferable to mix the powdered or granular material 14 containing moisture and the dry powdered or granular material 14 before classifying them by the movable sieve classifier 10.
[0108] However, the powdered and granular material 14 containing moisture may contain coarse particles having a size of about 10 to 20 mm or more. In this case, the powdered and granular material 14 containing moisture may be classified to separate and remove the coarse particles before mixing the powdered and granular material 14 containing moisture with the dry powdered and granular material 14. When separating and removing the coarse particles, the mesh of the sieving device can be made larger, so that the powdered and granular material 14 containing moisture is less likely to adhere to the mesh of the sieving device. There is a concern that the coarse particles may have a negative effect on the equipment. For example, the coarse particles may get caught in a rotating object in the mixing device, causing an overload and causing equipment failure. The separated and removed coarse particles may be charged into a blast furnace or the like.
[0109] In the above embodiment, the powdery material 14 is produced using zinc-containing iron-based waste material 1 as one of the raw materials. However, zinc-free iron-based dust may be used as the raw material instead of the iron-based waste material 1. If the raw material of the powdery material 14 does not contain zinc, dezincification does not need to be considered (reduction treatment of iron oxide is essential). In addition, powdery dust or slag (e.g. steelmaking slag) containing metallic iron or calcium oxide-containing compounds generated in the iron-making process may be used as the powdery material 14 as it is without reduction roasting treatment. In this case, all steps for producing the powdery material 14 can be omitted.
[0110] Steelmaking slag is a by-product of the iron making process, for example, desulfurization slag. Steelmaking slag contains metallic iron and calcium oxide-containing compounds such as calcium silicate. Carbon-containing agglomerates 21 produced from steelmaking slag have a high calcium content and can be used as a calcium source in a blast furnace. For example, when a large amount of acidic raw materials is charged into a blast furnace, the basicity of the slag generated in the blast furnace is optimized by charging the carbon-containing agglomerates 21 produced from steelmaking slag, and the discharge of molten slag is stabilized. In this way, steelmaking slag, which is a by-product of the iron making process, can be used as a substitute for calcium sources such as limestone. In addition, since steelmaking slag also contains iron, it is expected that steelmaking slag can also be used as an iron source. EXAMPLES
[0111] [First Example] In order to confirm the effect of the manufacturing method of the above embodiment, five kinds of powdery granular materials (samples K, L, M, N, O) were prepared. The powdery granular materials of samples K, L, M, N, O were used as raw materials to manufacture carbon-containing agglomerates 21 by tableting. The crushing strength of the manufactured carbon-containing agglomerates 21 was then examined. The powdery granular materials of samples K, L, M, N, O were either the powdery granular materials of samples A, D, H, I, J, or any of the samples mixed with steel dust having a carbon concentration of 35.6 mass%. Specifically, sample K was a powdery granular material obtained by adding 4 mass% of steel dust to sample A. Sample L was a powdery granular material obtained by adding 4 mass% of steel dust to sample D. Sample M was a powdery granular material obtained by adding sample H. Sample N was a powdery granular material obtained by adding 4 mass% of steel dust to sample I. Sample O was a powdery granular material obtained by adding sample J. The compositions of the samples A, D, H, I, J and the steel dust used in this example are shown in Table 2. The compositions of the samples K, L, M, N and O used as the raw material of the carbon-containing agglomerate 21 in this example are shown in Table 3.
[0112] [Table 2]
[0113] [Table 3]
[0114] Sample A is reduced iron obtained by reducing iron ore with carbon monoxide gas, and is the same as Sample A shown in Table 1. Sample D is powdered reduced iron obtained by subjecting iron-based waste to a reduction roasting process, and is the same as Sample D shown in Table 1. Sample H is a sample obtained by granulating iron ore powder mixed with coke powder, and heating at 1100°C while passing nitrogen through it. Sample H is reduced iron with a metallic iron content of 48.6% by mass, a calcium oxide content of less than 0.1% by mass (considered to be zero), and a carbon content of 3.7% by mass. Sample I is a sample obtained by subjecting iron-based waste to a reduction roasting process. Sample I is reduced iron with a metallic iron content of 17.9% by mass, a calcium oxide content of 16.2% by mass, and a carbon content of 1.4% by mass. Sample J is a steelmaking slag having a metallic iron content of 33.3 mass%, a calcium oxide content of 28.3 mass%, and a carbon content of 5.7 mass%.
[0115] Carbon analysis of each of the samples A, D, H, I, and J shown in Table 2 was performed by infrared absorption method using an infrared absorption apparatus. The infrared absorption apparatus is composed of a combustion extraction section, a detection section, and a data processing section. The target sample (sample) and combustion improver (tin) were placed on a ceramic combustion boat and charged into the combustion extraction section, and oxygen was circulated and burned in an atmosphere of 1350°C. As a result, the carbon in the sample became carbon dioxide. When infrared rays were irradiated on the gas generated by combustion, the carbon dioxide in the gas absorbed the infrared rays. The carbon dioxide concentration of the gas was calculated from the amount of absorption. Furthermore, the cumulative mass of carbon was calculated from the carrier gas flow rate and the carbon dioxide concentration, and the mass of carbon contained in the sample was calculated. This value was divided by the mass of the sample to calculate the carbon content of the sample.
[0116] However, carbon detected by infrared absorption method includes carbon present as carbonates such as calcium carbonate. Carbon present as carbonates does not contribute to the reduction reaction of iron oxide or heat source, and is not effective carbon for use in blast furnaces. Therefore, carbon present as carbonates must be excluded from consideration. In order to exclude carbon present as carbonates during carbon analysis, the following treatment was performed before measurement with the infrared absorption apparatus. First, the sample was dried at 105°C for 4 hours and crushed to a particle size of 212 μm or less. 0.25 g of the crushed sample was placed in a beaker, and 20 mL of a solution of hydrochloric acid and water mixed at a 1:1 (volume ratio) was added thereto. Furthermore, the carbonates contained in the sample were heated and dissolved while stirring the solution. After that, the solution was suction filtered using an aspirator, and the residue was collected. After drying the residue, the carbon analysis of the residue was performed using the infrared absorption apparatus.
[0117] In this embodiment, the moisture content of the powdered or granular material of each of the samples K, L, M, N, and O was adjusted to 4.0% by mass, and then cold tableting was performed. FIG. 6 is a schematic diagram showing the tableting process. Referring to FIG. 6, in the tableting process, the powdered or granular material 14 was put into a cylindrical die 22 under room temperature conditions, and the powdered or granular material 14 was compressed by applying a molding load of 5 tf. This produced a cylindrical tablet 23 having a diameter of 28 mm and a height of about 12 mm. The tablet 23 was subjected to a water immersion process in which the tablet 23 was immersed in a water tank 25 filled with water 24 for 60 seconds. After the water immersion process, the tablet 23 was subjected to a static process in which the tablet 23 was left statically in the air for 7 days. After the static process, the tablet 23 was placed horizontally (with the side of the cylinder in contact with the ground surface), and a crushing load was applied vertically from above the tablet 23 to measure the crushing strength.
[0118] The results of this example are shown in Table 4. Hereinafter, the crushing strength of the carbon-containing agglomerates 21 produced from the powdery and granular materials of each of Samples K, L, M, N, and O will be described as Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3, Example 1-1, and Example 1-2, respectively.
[0119] [Table 4]
[0120] Comparative Example 1-1 is a carbon-containing agglomerate 21 produced from the powdery material of sample K. The metallic iron content a of sample K was 25.2 mass% (0.252), the calcium oxide content b was 0.1 mass% (0.001), and the carbon content c was 1.4 mass% (0.014). The ratio of the total amount of calcium to the total amount of silicon contained in sample K was 0.06 (Ca / Si=0.06) in terms of mass ratio, which was outside the range of 2.9 to 6.1. In addition, the right side of the above formula (1) was 178 (=(2340×0.252+3300×0.001−400)×(1−5.5×0.014)), which did not satisfy the above formula (1). An attempt was made to produce a tablet 23 from this sample K, but the tablet 23 could not be produced due to poor moldability. The carbon content c of sample K is lower than the carbon content (2.5 mass % or more) of the powdered or granular material used in the manufacturing method according to the embodiment. However, it is unlikely that the moldability of the tablet 23 will be improved even if the carbon content of sample K is increased.
[0121] Comparative Example 1-2 is a carbon-containing agglomerate 21 produced from the powdery material of Sample L. The metallic iron content a of Sample L was 9.4 mass% (0.094), the calcium oxide content b was 15.7 mass% (0.157), and the carbon content c was 1.6 mass% (0.016). The ratio of the total amount of calcium to the total amount of silicon contained in Sample L was 3.6 (Ca / Si=3.6) in terms of mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 308 (=(2340×0.094+3300×0.157-400)×(1-5.5×0.016)), which did not satisfy the above formula (1). The crushing strength of the tablets 23 produced from this Sample L was 315 N / piece, which was smaller than the crushing strength (400 N / piece) required for a blast furnace raw material. The carbon content c of sample L is lower than the carbon content (2.5 mass% or more) of the powdered or granular material used in the manufacturing method according to the embodiment. However, if the carbon content of sample L is increased, the crushing strength of tablet 23 is considered to be further decreased.
[0122] Comparative Example 1-3 is a carbon-containing agglomerate 21 produced from the powdery material of Sample M. The metallic iron content a of Sample M was 48.6 mass% (0.486), the calcium oxide content b was less than 0.1 mass% (considered to be zero), and the carbon content c was 3.7 mass% (0.037). The ratio of the total amount of calcium to the total amount of silicon contained in Sample M was zero (Ca / Si=0) in mass ratio, which was outside the range of 2.9 to 6.1. The right side of the above formula (1) was 585 (=(2340×0.486+3300×0−400)×(1−5.5×0.037)), which satisfied the above formula (1). The crushing strength of the tablets 23 produced from this Sample M was 286 N / piece, which was smaller than the crushing strength required for a blast furnace raw material. From this, it is considered that in order to increase the crushing strength of the tablet 23, it is necessary to have the powdered material contain a certain amount of calcium.
[0123] Example 1-1 is a carbon-containing agglomerate 21 produced from the powdery material of sample N. The metallic iron content a of sample N was 17.2 mass% (0.172), the calcium oxide content b was 15.7 mass% (0.157), and the carbon content c was 2.8 mass% (0.028). The ratio of the total amount of calcium to the total amount of silicon contained in sample N was 3.7 (Ca / Si=3.7) in mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 440 (=(2340×0.172+3300×0.157−400)×(1−5.5×0.028)), which satisfied the above formula (1). The crushing strength of the tablets 23 produced from this sample N was 430N / piece, which was greater than the crushing strength required for a blast furnace raw material.
[0124] Example 1-2 is a carbon-containing agglomerate 21 produced from the powdery material of sample O. The metallic iron content a of sample O was 33.3 mass% (0.333), the calcium oxide content b was 28.3 mass% (0.283), and the carbon content c was 5.7 mass% (0.057). The ratio of the total amount of calcium to the total amount of silicon contained in sample O was 4.3 (Ca / Si=4.3) in mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 903 (=(2340×0.333+3300×0.283-400)×(1-5.5×0.057)), which satisfied the above formula (1). The crushing strength of the tablet 23 produced from this sample O was 1019 N / piece, which was greater than the crushing strength required for a blast furnace raw material.
[0125] [Second Example] In this embodiment, five kinds of powdery granular materials (samples R, S, T, U, and V) were prepared. The powdery granular materials of samples R, S, T, U, and V were used as raw materials to manufacture the carbon-containing agglomerates 21 by briquetting. The crushing strength of the manufactured carbon-containing agglomerates 21 was examined. Two kinds of reduced iron were prepared as raw materials for each of samples R, S, T, U, and V. These reduced irons are called powdery granular reduced iron P and powdery granular reduced iron Q. The powdery granular materials of samples R, S, T, U, and V are either powdery granular reduced iron P or Q, or are powdery granular materials obtained by mixing either of them with coke powder or steel dust. Specifically, sample R is powdery granular reduced iron P. Sample S is a powdery granular material obtained by adding 2 mass % of coke powder to powdery granular reduced iron Q. Sample T is a powdery granular material obtained by adding 4 mass % of steel dust to powdery granular reduced iron Q. Sample U is a powdered material obtained by adding 6 mass% of steel dust to granular reduced iron Q. Sample V is a powdered material obtained by adding 8 mass% of steel dust to granular reduced iron Q. The compositions of the granular reduced irons P and Q, coke powder, and steel dust used in this example are shown in Table 5. Table 6 shows the compositions of samples R, S, T, U, and V used as the raw materials for the carbon-containing agglomerated ore 21 in this example.
[0126] [Table 5]
[0127] [Table 6]
[0128] The powdered reduced iron P, Q was produced in the same manner as in the preparation step (#5) of the production method according to the embodiment. Specifically, the mixed raw material 6, which was a mixture of the iron-based waste material 1a, the iron-based waste material 1b, the carbonaceous material 2, and the calcium-containing material 3 (milk of lime), was reduced and roasted in a rotary kiln 7. In the reduction roasting process, the amount of the calcium oxide-containing compound added was adjusted so that the ratio of calcium to silicon contained in the mixed raw material was 3.3 to 4.3 in mass ratio. The baking point temperature (the maximum temperature in the rotary kiln 7) in the reduction roasting process was 1180 to 1260°C, which was lower than 1300°C. The reduced iron 8 after the reduction roasting process was cooled, and then the obtained reduced iron was classified using a sieve classification device with a mesh size of 4.75 mm, and the undersized product was used as the powdered reduced iron P, Q.
[0129] Carbon analysis of the fine reduced irons P and Q and the steel dust shown in Table 5 was performed by infrared absorption method as in Example 1. Carbon analysis of the coke powder was performed in accordance with JIS M8812 (2006) as described above.
[0130] In this embodiment, the moisture content of the powdered material of sample R was adjusted to 2.0% by mass, and the moisture content of the powdered material of samples S, T, U, and V was adjusted to 4.0% by mass. Then, the powdered material of each of samples R, S, T, U, and V was subjected to cold briquetting. For the briquetting, a double-roll type briquette molding machine (agglomeration device 17) shown in FIG. 4 was used. The diameter of the rolls 171 and 172 of the agglomeration device 17 was 228 mm, and the effective width was 32 mm. The pockets 171a and 172a were provided in a row in the width direction of the rolls 171 and 172, and 36 positions were provided along the circumferential direction. The size of the pockets 171a and 172a was 28 mm vertically (the length in the width direction of the roll), 18 mm horizontally (the length in the circumferential direction of the roll), and 4 mm deep. The volume of the briquettes produced by the agglomeration device 17 was about 3 cm 3 It was.
[0131] The total compression load applied to the rolls 171, 172 was controlled to be 17 to 18 t (tons). In other words, the compression line pressure (=total compression load applied to the rolls / effective width of the rolls) of the agglomeration device 17 was 5.3 to 5.6 t / cm. The rotation speed of the screw installed inside the hopper above the rolls 171, 172 was automatically controlled so that the range of the compression load would not deviate from the set value. In other words, when the compression load applied to the rolls 171, 172 is likely to be less than 17 tons, the rotation speed of the screw is increased to increase the supply amount of the powdered material 14 supplied to the pockets 171a, 172a, so that the powdered material 14 can be supplied to the inside of the pockets 171a, 172a with a higher packing density. This allows the compression load to be controlled to be high. Conversely, when the compressive load on the pockets 171a, 172a was likely to exceed 18 tons, the rotation speed of the screw was slowed down to reduce the amount of powdered material 14 supplied to the rolls 171, 172, thereby controlling the compressive load to be lower.
[0132] The briquette thus produced was subjected to a water immersion treatment by submerging it in a container filled with water for 60 seconds. After the water immersion treatment, the briquette was subjected to a static treatment by leaving it in the air for 6 days. After the static treatment, the briquette was placed horizontally (with the thickness direction of the briquette vertical) and a crushing load was applied vertically from above the briquette to measure the crushing strength.
[0133] The results of this example are shown in Table 7. Hereinafter, the crushing strength of the carbon-containing agglomerates 21 produced from the powdery and granular materials of each of Samples R, S, T, U, and V will be described as Example 2-1, Example 2-2, Example 2-3, Example 2-4, and Example 2-5, respectively.
[0134] [Table 7]
[0135] Example 2-1 is a carbon-containing agglomerated ore 21 produced from the powdery material of sample R. The metallic iron content a of sample R was 31.5 mass% (0.315), the calcium oxide content b was 18.6 mass% (0.186), and the carbon content c was 4.0 mass% (0.040). The ratio of the total amount of calcium to the total amount of silicon contained in sample R was 4.3 (Ca / Si=4.3) in terms of mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 742 (=(2340×0.315+3300×0.186−400)×(1−5.5×0.040)), which satisfied the above formula (1). The crushing strength of the briquette produced from this sample R was 1568 N / piece, which was greater than the crushing strength required for a blast furnace raw material. The mass of each briquette was 12.1 g.
[0136] Example 2-2 is a carbon-containing agglomerate 21 produced from the powdery material of sample S. The metallic iron content a of sample S was 23.9 mass% (0.239), the calcium oxide content b was 14.9 mass% (0.149), and the carbon content c was 2.8 mass% (0.028). The ratio of the total amount of calcium to the total amount of silicon contained in sample S was 3.6 (Ca / Si=3.6) in terms of mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 551 (=(2340×0.239+3300×0.149-400)×(1-5.5×0.028)), which satisfied the above formula (1). The crushing strength of the briquette produced from this sample S was 1245 N / piece, which was greater than the crushing strength required for a blast furnace raw material. The mass of each briquette was 12.2 g.
[0137] Example 2-3 is a carbon-containing agglomerate 21 produced from the powdery material of sample T. The metallic iron content a of sample T was 23.4 mass% (0.234), the calcium oxide content b was 14.7 mass% (0.147), and the carbon content c was 2.5 mass% (0.025). The ratio of the total amount of calcium to the total amount of silicon contained in sample T was 3.5 (Ca / Si=3.5) in mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 546 (=(2340×0.234+3300×0.147−400)×(1−5.5×0.025)), which satisfied the above formula (1). The crushing strength of the briquette produced from this sample T was 1283 N / piece, which was greater than the crushing strength required for a blast furnace raw material. The mass of each briquette was 12.1 g.
[0138] Example 2-4 is a carbon-containing agglomerate 21 produced from the powdery material of sample U. The metallic iron content a of sample U was 23.0 mass% (0.230), the calcium oxide content b was 14.5 mass% (0.145), and the carbon content c was 3.2 mass% (0.032). The ratio of the total amount of calcium to the total amount of silicon contained in sample U was 3.4 (Ca / Si=3.4) in mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 508 (=(2340×0.230+3300×0.145−400)×(1−5.5×0.032)), which satisfied the above formula (1). The crushing strength of the briquette produced from this sample U was 1232 N / piece, which was greater than the crushing strength required for a blast furnace raw material. The mass of each briquette was 12.1 g.
[0139] Example 2-5 is a carbon-containing agglomerate 21 produced from the powdery material of sample V. The metallic iron content a of sample V was 22.5 mass% (0.225), the calcium oxide content b was 14.3 mass% (0.143), and the carbon content c was 3.9 mass% (0.039). The ratio of the total amount of calcium to the total amount of silicon contained in sample V was 3.3 (Ca / Si=3.3) in mass ratio, which was within the range of 2.9 to 6.1. The right side of the above formula (1) was 470 (=(2340×0.225+3300×0.143−400)×(1−5.5×0.039)), which satisfied the above formula (1). The crushing strength of the briquette produced from this sample V was 1106 N / piece, which was greater than the crushing strength required for a blast furnace raw material. The mass of each briquette was 11.9 g.
[0140] In Examples 2-1, 2-2, 2-3, 2-4, and 2-5, the crushing strength of the briquettes actually produced was greater than the right side of the above formula (1). As described above, the above formula (1) was derived using tabletted carbon-containing agglomerates. On the other hand, in this example, carbon-containing agglomerates briquetting using a double-roll briquetting machine were used. This shows that the strength of the carbon-containing agglomerates obtained is improved when a double-roll briquetting machine is used as the agglomeration device.
[0141] In this example, the mixed raw material before reduction roasting and the powdered reduced irons P and Q after reduction roasting in the rotary kiln were irradiated with X-rays. It was examined whether the peaks of the compounds contained in the mixed raw material and the powdered reduced irons P and Q were detected by this X-ray diffraction. The results of the X-ray diffraction are shown in Table 8.
[0142] [Table 8]
[0143] As shown in Table 8, no peaks of dicalcium silicate (2CaO·SiO2) were detected in the mixed raw materials. On the other hand, peaks of dicalcium silicate, a compound of calcium oxide and silicon dioxide that increases the strength of carbon-bearing agglomerates, were detected in the powdered reduced iron P and granular reduced iron Q. From this, it is considered that dicalcium silicate was generated in the rotary kiln during the reduction roasting process. When the mixed raw materials are mixed, it is considered that by setting the ratio of the total amount of calcium to the total amount of silicon contained in the raw materials to 2.9 or more by mass ratio, it is easier to generate strength-increasing components such as dicalcium silicate (Ca / Si=2.9) or tricalcium silicate (Ca / Si=4.3) during the reduction roasting process. In addition, silicon dioxide contained in dicalcium silicate is contained in the iron-based waste material that serves as the iron source, or the carbonaceous material that serves as the fuel or reducing agent during the operation of the rotary kiln. In other words, the silicon contained in the dicalcium silicate generated in the rotary kiln is not silicon (SiO2) added as a binder. In this example, a calcium source such as lime was added to the iron-based waste material or carbonaceous material so that the ratio of the total amount of calcium to the total amount of silicon was 2.9 or more (Ca / Si≧2.9) by mass ratio. In addition, milk of lime, which is a suspension of very fine lime powder in water, was used as the calcium source. This is thought to promote the contact and reaction between silicon and calcium, accelerating the production of di-calcium silicate.
[0144] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure. [Explanation of symbols]
[0145] 1, 1a, 1b: Iron-based waste materials 2:Charcoal material 3: Calcium-containing substances 4: Conveyor belt 5: Mixing device 6: Mixed raw materials (raw materials) 7: Rotary kiln 8: Reduced iron 9: Cooling device 10: Movable screening and classification device 11: Lumpy material 12: Screen undersize 13: Carbon-containing material 14: Powder and granular material 15: Mixing device 16: Lump-forming product 17: Lump-forming device 171, 172: Roll 171a, 172a: Pocket 18: Screening and classification device 19: Water immersion treatment device 20: Water 21: Carbon-containing lump ore 22: Die 23: Tablet 24: Water 25: Water tank
Claims
1. a preparation step of preparing a powdered or granular material containing metallic iron and a calcium oxide-containing compound, the powdered or granular material having a total iron content of 10 mass% or more on a dry basis, a carbon content of 2.5 mass% or more, a ratio of a total amount of calcium to a total amount of silicon of 2.9 to 6.1 in mass ratio, and the metallic iron content a, calcium oxide content b, and carbon content c satisfying the following formula (1); a moisture adjusting step of adjusting the moisture content of the powdery or granular material to 0.5% by mass or more and 7.0% by mass or less; an agglomeration step of cold compressing and agglomerating the powdery or granular material to form an agglomerate after the moisture adjusting step; a water immersion step of subjecting the agglomerates to a water immersion treatment; the water immersion step being followed by a standing step of subjecting the agglomerates to a standing treatment. 400≦(2340×a+3300×b−400)×(1−5.5×c) (1)
2. The method for producing carbon-containing agglomerates according to claim 1, A method for producing carbon-containing agglomerates, wherein in the preparing step, the content a of metallic iron in the powdery ore is 10 mass% or more.
3. The method for producing carbon-containing agglomerates according to claim 1, A method for producing carbon-containing agglomerates, wherein in the preparing step, a calcium oxide content b of the powdery ore is 10 mass % or more and 40 mass % or less.
4. The method for producing carbon-containing agglomerates according to claim 1, A method for producing carbon-containing agglomerates, wherein in the preparing step, the content of the high silicon-based binder in the powdery ore is 2 mass % or less on a dry basis.
5. The method for producing carbon-containing agglomerates according to claim 1, In the preparation step, the powdery ore is produced by subjecting raw materials including iron-based waste materials to a reducing roasting treatment.
6. The method for producing carbon-containing agglomerates according to claim 5, In the preparation step, the raw materials include the iron-based waste material, the carbonaceous material, and the calcium-containing substance, The iron-based scrap material or the carbonaceous material contains a silicon-containing material, A method for producing carbon-containing agglomerates, wherein a ratio of calcium to silicon contained in the raw materials is 2.9 or more and 6.1 or less in terms of mass ratio.
7. The method for producing carbon-containing agglomerates according to claim 6, In the preparing step, the calcium-containing material contained in the raw materials is in the form of a slurry in which lime powder is suspended in water.
8. The method for producing carbon-containing agglomerates according to claim 5, The method for producing carbon-containing agglomerates, wherein in the preparation step, the reduction roasting treatment is carried out at a temperature of less than 1,300°C.
9. The method for producing carbon-containing agglomerates according to claim 5, In the preparation step, reduced iron is produced by the reduction roasting treatment, a mass ratio of the metallic iron to the iron content contained in the reduced iron is 0.8 or less.
10. The method for producing carbon-containing agglomerates according to claim 1, In the agglomeration step, the powdery or granular material is compressed and agglomerated using an agglomeration device, and then sieved to classify the agglomerated material into an oversieve product and an undersieve product of the powdery or granular material; the powdery ore which is an undersize product is supplied to the agglomeration device and compressed and agglomerated again.
11. The method for producing carbon-containing agglomerates according to claim 1, wherein the mass of each of the agglomerates after the standing step is 40 g or less.
12. The method for producing carbon-containing agglomerates according to claim 1, The method for producing carbon-containing agglomerates, wherein the standing step comprises standing treatment in an atmosphere of 5° C. or higher and lower than 50° C.
13. The method for producing carbon-containing agglomerates according to claim 1, In the agglomeration step, the powdery ore is compressed and agglomerated using a double roll briquetting machine.
Citation Information
Patent Citations
Adhesive admixture for construction and its manufacture
JP1980003364A
Terpolymer
JP1980003495A
Accelerating fuel passage system in multiicarburetor
JP1980012205A
Agglomerate for reduced iron and its production
JP1999092833A
Method for producing agglomerate with carbon material interior
JP3502008B2